PARALLELS IN THE WORKS OF AZHINIYAZ KASYBAY UULU AND ARSTANBEK BUYLASH UULU - Кolbaeva М. К. (Vestnik Issyk-Kulʹskogo universiteta)
In the above article our aim was to analyze parallels in the works of Karakalpak poet Azhiniyaz Kasybay uulu and Kyrgyz poet Arstanbek akyn. Born in the same year, one lived in the Khanate of Khiva and the other lived on Kyrgyz soil. Both poets wrote the fate of Kyrgyz people who grew up from lack of life from the time they were born to the last years of their lives. And also he gave advice to the ruler of the people, showed the way. He wrote different folk works arman, koshok, aytysh and thematic varieties of lyrics, in parallel came up with ideas of lyrical works. This confirms that both poets are folk poets of their people.